Magnesium oxychloride cement-based strain-hardening cementitious composite: Mechanical property and water resistance. (20th November 2020) - Yu, Kequan; Guo, Yingying; Zhang, Y.X.; Soe, Khin
Highlights: High-strength, high-ductility MOC-SHCC is developed. MOC-SHCC demonstrates high-early-strength characteristic. Addition of PE fiber increases the water-resistance of MOC mortar. Abstract: A new category of magnesium oxychloride cement-based strain-hardening cementitious composites (MOC-SHCC) with high-strength and high-ductility is developed in this research. The eco-friendly and high-strength MOC mortar is used as the matrix and ultra-high-molecular-weight polyethylene (PE) fiber is deployed as reinforcement. The development of mechanical properties of the MOC-SHCC with the curing ages varying from 12 h (h) to 28 days (d) is fully investigated and the high-early-strength characteristic of MOC-SHCC is demonstrated. The compressive, flexural, and tensile strength of the MOC-SHCC at 1d reach 71.4 MPa, 25.2 MPa, and 8.28 MPa respectively, accounting for 56%, 84%, and 75% of the corresponding values at 28d. The tensile capacities of the MOC-SHCC decrease slightly with the curing age, while all the values are beyond 6% accompanying with the evenly distributed microcracks. Additionally, water resistance of the MOC-SHCC is systematically investigated by using an accelerating method through immersing specimens into 60 °C hot water for 7d and 28d at the curing ages of 1d, 3d and 28d, respectively. The developed high-performance MOC-SHCC features with high early strength, high ductility, and satisfactory water resistance, which would have a strong potential application in practical engineering.